Risk factors for conversion to arthroplasty after hip arthroscopy for femoroacetabular impingement - Oliveira, José Ricardo; Dinis, João; Sarmento, André; Lemos, Rui (International Journal of Research in Orthopaedics, 2023)
Background: Hip arthroscopy is a surgical procedure that is increasingly used worldwide, mostly in the management of femoroacetabular impingement (FAI). The purpose of this study is to evaluate risk factors for conversion of hip arthroscopy to THA within 3 years after the procedure. Methods: Hip arthroscopies for FAI performed at our institution between 2013 and 2019 were reviewed. Inclusion criteria included a minimum 3-year follow-up or a conversion to THA within 3 years. Patient characteristics and radiographic evaluation was made for each patient. This collected data were compared in the two groups Total hip arthroplasty vs non total hip arthroplasty (THA vs non-THA). Results: A total of 136 patients met the inclusion criteria (69 men, 67 women, mean age 38,21 years). During the follow-up period, 22 underwent a THA in less than 3 years after the procedure (16.2%). A statistically significant association was found between conversion to THA and the Tönnis grade (p<0.05), Kellgren-Lawrence grade (p<0.05) and the joint space (p<0.05). It was also found that the patient’s age, body mass index (BMI), race and sex did not add independent predictive information. Conclusions: Our analysis demonstrates a strong and significant association between the radiographic evaluation of osteoarthritis (Tönnis grade, Kellgren-Lawrence grade and joint space narrowing) and the risk of early conversion to THA. Other patient characteristics, like patient’s age, BMI, race and sex, doesn´t seem to increase the risk.